(untitled) (Bangladesh Critical Care Journal, 2024)
Background: Lung protective strategy in acute respiratory distress syndrome (ARDS) patients is based on low tidal volume (VT), lower end-inspiratory (plateau) pressure and higher positive end-expiratory pressure (PEEP). But to predict body weight adjusted tidal volume, heterogeneous pathology of the lung in ARDS with different respiratory system compliance (CRS) is not considered. In driving pressure (ΔP=VT / CRS) tidal volume (VT) is normalized to functional lung size. It is unclear whether mechanical ventilation targeting driving pressure (ΔP) is more effective than low tidal volume ventilation (LTVV) in patients with ARDS. Materials and Methods: An open labelled randomized controlled trial was conducted at Intensive Care Unit of Dhaka Medical College Hospital, a tertiary care referral hospital over 12 months from March 2021 to February 2022. Ninety two patients with ARDS, defined by the Berlin criteria, requiring mechanical ventilation were randomized to 1:1 ratio after enrollment in the study using simple random sampling, one group receiving targeted driving pressure (ΔP) that is </=14cm of H2O ventilation another group receiving low tidal volume ventilation (LTVV) that is 4-6ml/kg PBW. Results: The study found no significant differences between the two groups in terms of clinical variables and laboratory parameters (p > 0.05), except for the duration of mechanical ventilation (MV), which was significantly shorter in the Targeted ΔP group (p<0.05). Aspiration pneumonia was the most common cause of ARDS, occurring in 34.8% of the Targeted ΔP group and 39.1% of the LTVV group. The Targeted ΔP group demonstrated a significant increase in mean respiratory system compliance compared to the LTVV group (p<0.001), and a significantly shorter length of ICU stay (p <0.001). Additionally, the PaO2/FiO2 ratio was significantly higher in the Targeted ΔP group on Days 3, 5, and 7 (p<0.05). Mean exhaled tidal volume was also significantly higher in the Targeted ΔP group on these days (p<0.05). In the Targeted ΔP group, mean driving pressure significantly decreased on Days 3, 5, and 7 (p <0.001), along with a significant reduction in mean plateau pressure (PPlt) (p <0.001). Mean positive end-expiratory pressure (PEEP) significantly decreased on Days 3, 5, and 7 (p <0.001). Respiratory rate significantly decreased on Day 7 (p <0.05). Mean set tidal volume (VT) significantly increased on Days 3, 5, and 7 (p <0.001). Moreover, the 28-day mortality incidence was significantly lower in the Targeted ΔP group compared to the LTVV group (8.7% vs. 26.1%, p <0.05). Conclusion: Targeted Driving pressure (ΔP) guided ventilation offers significant clinical benefits over LTVV in managing ARDS patients in terms of increased respiratory system compliance (CRS), shorter lengths of hospital and ICU stays, and lower in-hospital mortality. Bangladesh Crit Care J September 2024; 12 (2): 81-88